Effects of Nitrate and Salinity on Fatty Acid Composition of Marine Tetraselmis sp.: Potential as Biodiesel - Noriko, Nita; Prayitno, Joko; Anggraini, Bunga (UI Scholars Hub, 2015)
Identifying sources of renewable energy is extremely important. The potential of Tetraselmis sp. in biodiesel production was investigated using a completely randomized design with four treatments. Tetraselmis sp. was cultured on media containing different concentrations of nitrate there are 2 mM and 15 Mm and s 25 ‰ and 35 ‰ salinity. The treatments namely are (N2S25), (N2S35), N15S25) and (N15S35). Analysis of the fatty acid content using gas chromatography-mass spectrometry (GC-MS). The results showed that the highest growth occurred in culture that contained 15 mM of nitrate and 35 ‰ salinity. The lowest growth occurred in culture containing 2 mM of nitrate and 25‰ of salinity. The highest lipid content was found in cultures containing 2 mM of nitrate and 25‰ salinity, it is 34.83%. Seven fatty acids were detected in culture containing 2 mM of nitrate and 25‰ salinity namely myristic acid (4.02%), palmitic acid (40.59%), palmitoleic acid (29.06%), stearic acid (0.95%), oleic acid (12.52%), gamma-linolenic acid (2.56%), and arachidonic acid (9.38%). Four fatty acids palmitoleic acid (8.99%), palmitic acid (37.34%), oleic acid(44.89%), and stearic acid (8.78%) were detected in 2 mM of nitrate with 35‰ salinity. The fatty acids have potential to be used as raw material for biodiesel production.